2010
DOI: 10.4314/bajopas.v2i1.58472
|View full text |Cite
|
Sign up to set email alerts
|

A survey of ecto and intestinal parasites of <i>Tilapia Zillii</i> (Gervias) in Tiga lake, Kano, northern Nigeria

Abstract: One thousand eight hundred specimens of Tilapia zillii (Gervias) from Tiga Lake, Kano, Northern Nigeria were examined using hand lens and microscope between July, 2007 and June 2008 for parasites , 782 (53.4%) of these were infected. Parasites recovered were, Clinostomum spp. 74(4.1%) Procamellanus spp. 111 (6.1%), and Protozoa Cyst 198 (11.0%). Adult fishes were more infected than the juvenile, females were significantly more infected (P <0.05). Infection increases with length and body weight. Physio-chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
28
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 1 publication
14
28
3
Order By: Relevance
“…The present findings are nearly similar to observations detected by many authors including (Bichi and Ibrahim, 2009). The overall mean pH values was significantly higher at ponds water this may be due to the increase in pH value in water with high photosynthetic rate and the depletion of carbon dioxide.…”
Section: Discussionsupporting
confidence: 83%
“…The present findings are nearly similar to observations detected by many authors including (Bichi and Ibrahim, 2009). The overall mean pH values was significantly higher at ponds water this may be due to the increase in pH value in water with high photosynthetic rate and the depletion of carbon dioxide.…”
Section: Discussionsupporting
confidence: 83%
“…In general, the overall prevalence of 50.00% of parasites observed in this study is comparatively lower than the prevalence of 53.49% and 60.66% documented by Bichi and Ibrahim [26] and Nmor et al [18]. Similarly, the prevalence values obtained in the current study is higher than 15.80%, 20.83%, 29.17% and 38.00% recorded by Oribhabor et al [8], Bekele and Hussien [15], Edeh and Solomon [27], Biu and Akorede [5], respectively.…”
Section: Discussioncontrasting
confidence: 79%
“…Accordingly, results revealed a higher parasite infestation in longer (>30cm) and large sized (500-1000g) fish classes. Similarly, Allumma and Idowu (2011) and Bichi and Ibrahim (2009) have found that larger fish were heavily parasitized than the smaller ones. The prevalence of parasite infection increased with increasing length, size and age of the fish host as it increases their chance of acquiring the parasite infection with time and increased size as well.…”
Section: Discussionmentioning
confidence: 79%